Clinical Outcomes in Patients with Deferred Coronary Lesions according to Disease Severity Assessed by Fractional Flow Reserve - Won, Ki-Bum; Nam, Chang-Wook; Cho, Yun-Kyeong; Yoon, Hyuck-Jun; Park, Hyoung-Seob; Kim, Hyungseop; Han, Seongwook; Hur, Seung-Ho; Kim, Yoon-Nyun; Park, Sang-Hyun; Han, Jung-Kyu; Koo, Bon-Kwon; et al. (Journal of Korean medical science, 2016)
Data on the clinical outcomes in deferred coronary lesions according to functional severity have been limited. This study evaluated the clinical outcomes of deferred lesions according to fractional flow reserve (FFR) grade using Korean FFR registry data. Among 1,294 patients and 1,628 lesions in Korean FFR registry, 665 patients with 781 deferred lesions were included in this study. All participants were consecutively categorized into 4 groups according to FFR; group 1: ≥ 0.96 (n = 56), group 2: 0.86-0.95 (n = 330), group 3: 0.81-0.85 (n = 170), and group 4: ≤ 0.80 (n = 99). Primary endpoint was major adverse cardiac events (MACE), a composite of all-cause death, myocardial infarction, and target vessel revascularization. The median follow-up period was 2.1 years. During follow-up, the incidence of MACE in groups 1-4 was 1.8%, 7.6%, 8.8%, and 13.1%, respectively. Compared to group 1, the cumulative rate by Kaplan-Meier analysis of MACE was not different for groups 2 and 3. However, group 4 had higher cumulative rate of MACE compared to group 1 (log-rank P = 0.013). In the multivariate Cox hazard models, only FFR (hazard ratio [HR], 0.95; P = 0.005) was independently associated with MACE among all participants. In contrast, previous history of percutaneous coronary intervention (HR, 2.37; P = 0.023) and diagnosis of acute coronary syndrome (ACS) (HR, 2.35; P = 0.015), but not FFR, were independent predictors for MACE in subjects with non-ischemic (FFR ≥ 0.81) deferred coronary lesions. Compared to subjects with ischemic deferred lesions, clinical outcomes in subjects with non-ischemic deferred lesions according to functional severity are favorable. However, longer-term follow-up may be necessary.